University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 3 - Section 3.5 - Derivatives of Trigonometric Functions - Exercises: 28


$p' = -cot^{2}q - sinq -1=-sinq-cosec^2q$

Work Step by Step

$p = (1+cosecq)cosq$ $p' = (-cosecq\ cotq)cosq - (1+cosecq)sinq$ $p' = -cot^{2}q - sinq -1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.